HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN TINGKAT KELETIHAN PADA ANAK DENGAN KANKER POST KEMOTERAPI DI RUMAH SINGGAH YAYASAN PEDULI KANKER ANAK BALI - Yasih, Ni Putu Wahyu Santi; Utami, Kadek Cahya; Suindrayasa, I Made (Coping: Community of Publishing in Nursing; Vol 9 No 5 (2021): Oktober 2021, 2021)
Fatigue is cancer that can affect the child's quality of life. Many factors are associated with fatigue in children with cancer who get chemotherapy. This research aimed to identify the relantionship between body mass index with the level of fatigue children with post-chemotherapy cancer. This research also used quantitative methods with a cross-sectional approach. The sample in this research were 20 people selected using consecutive sampling techniques based on inclusion and exclusion criteria. The instruments used included demographic data questionnaire and fatigue level questionnaire (CSF and FS-A). Based on Spearman's Rank statistical test results obtained that body mass indexx (p = 0.001; r = -0.696) has a significant relationship with level of fatigue at Children's Cancer Concern Foundation. Research is expected to be a guideline for parents and foundations so that they can implement activities that do not aggravate the level of fatigue in children with post-chemotherapy cancer and nurses can provide interventions to minimize fatigue in children with post-chemotherapy cancer. Keywords: children with cancer, post-chemotherapy, and level of fatigue.